Conclusions. Le nouvel essor des recherches archéologiques à Baelo au xxie siècle - Pierre Sillières (Mélanges de la Casa de Velázquez)
The archaeological research carried out at Bolonia (Tarifa, Cádiz) from 1917 to 1921 and from 1964 to 1990 focused almost exclusively on the remains of the Hispano-Roman town. The investigations currently going on at the site have either resumed or continued that earlier research as in the case of the theatre, the aqueducts and the water supply system, the fish-salting works or the eastern necropolis or else they have been devoted to hitherto-unexcavated remains, such as the current work on the buildings south-east of the forum, a bath-house outside the walls or the oppidum of Silla del Papa, where it has been finally established that the original Baelo was located.